Hubungan Kadar Polusi Udara dengan Kejadian Tuberkulosis di Kota Pekanbaru Tahun 2015 sampai dengan 2020 - Suyanto Suyanto; Salsabilla Aulia; Emillian Ramli; Fifia Chandra (Jurnal Ilmu Kedokteran, 2023)
Changes in air quality increase host susceptibility to Mycobacterium tuberculosis. Retrospective cohort study to see the relationship between air pollution levels and climate with tuberculosis cases in Pekanbaru City in 2015 – 2020. It found there is a significant positive correlation between PM10, SO2, CO, O3, NO2, PM2.5 and the number of tuberculosis cases per day. While in climate, temperature and humidity parameters do not provide a significant relationship, while rainfall and wind speed provide a very weak correlation strength with tuberculosis. We conclude there is a positive correlation air pollution and the number of tuberculosis cases per day.